Transforming Organizational Culture: A Roadmap for Successful Change Management - Sheila Kurnia Putri (PINISI Discretion Review, 2023)
Organizational culture is a critical factor that shapes the behavior and performance of employees and influences the overall success of the organization. However, changing the organizational culture can be challenging and requires a strategic and systematic approach to ensure its success. Therefore, this study aims to investigate the roadmap for successful change management in transforming organizational culture. The objective of this study is to explore the roadmap for successful change management in transforming organizational culture and provide practical guidance for organizations that are seeking to transform their culture.This study employs a qualitative research approach, and data were collected through semi-structured interviews with organizational development experts and change management practitioners. The data were analyzed using thematic analysis to identify common themes and patterns. The findings of this study reveal that a successful roadmap for transforming organizational culture involves several stages, including assessing the current culture, developing a vision for the desired culture, engaging stakeholders, communicating the vision, and implementing the change. Additionally, the study identified several critical success factors for change management, including leadership commitment, employee engagement, communication, and training.